Applying ontologies for workflow modelling and execution for a virtual ISP. (1st December 2008) - Pop, Daniel; Fortis, Teodor-Florin; Negru, Viorel
Small Internet Service Providers (ISPs) are constrained to resell the wholesale services of incumbent operators that own the access infrastructure. They struggle to gain competitive advantages by improving the typical services provided (e.g., e-mail, hosting) and through their capability to provide specific added-value services, which are more difficult for larger entities to offer. The production of tailored solutions targeted at the needs of local businesses is strongly facilitated by an appropriate conceptual and executable model of the ISP domain. Innovative technologies, like ontologies, web technologies, workflow technologies, network modelling and Directory Enabled Networks, are combined to build a platform that enables a cluster of Small- and Medium-sized Enterprises (SMEs) to operate as a single business entity. The goal of this paper is to highlight the role of ontologies in the implementation and execution of the aforementioned platform.